Dual Role of Mo6S8 in Polysulfide Conversion and Shuttle for Mg–S Batteries. Issue 7 (9th January 2022) - Wang, Liping; Jankowski, Piotr; Njel, Christian; Bauer, Werner; Li, Zhenyou; Meng, Zhen; Dasari, Bosubabu; Vegge, Tejs; Lastra, Juan Maria García; Zhao‐Karger, Zhirong; Fichtner, Maximilian
Abstract: Magnesium–Sulfur batteries are one of most appealing options among the post‐lithium battery systems due to its potentially high energy density, safe and sustainable electrode materials. The major practical challenges are originated from the soluble magnesium polysulfide intermediates and their shuttling between the electrodes, which cause high overpotentials, low sulfur utilization, and poor Coulombic efficiency. Herein, a functional Mo6 S8 modified separator is designed to effectively address these issues. Both the experimental results and density functional theory calculations show that the electrochemically active Mo6 S8 layer has a superior adsorption capability of polysulfides and simultaneously acts as a mediator to accelerate the polysulfide conversion kinetics. Remarkably, the magnesium–sulfur cell assembled with the functional separator delivers a high specific energy density (942.9 mA h g −1 in the 1st cycle) and can be cycled at 0.2 C for 200 cycles with a Coulombic efficiency of 96%. This work demonstrates a new design concept toward high‐performance metal–sulfur batteries. Abstract : A Mo6S8‐modified separator is utilized to suppress the polysulfide shuttle in Mg–S batteries. Based on experimental investigations and density functional theory calculations, the separator shows a superior adsorption capability of polysulfide and a catalytic effect on the polysulfide conversion reactions. Mg–S cells in both coin and pouch cell configurations can achieve high reversible capacities with extended cycle life.